PELATIHAN BERBAHASA INGGRIS UNTUK WARGA SEKITAR OBJEK WISATA DESA PASIR PUTIH LOMBOK - Nurazizah Nurazizah; Aurelius RL Teluma (Jurnal Warta Desa (JWD), 2019)
The residents of Pasir Putih village who live on the coast of Selong Belanak depend their livelihood on the work of fishermen and coastal tourism. This beach and village is located on the south coast of the Praya Barat sub-district, Central Lombok Regency, NTB. There are several problems faced by local communities, namely: 1) Low awareness regarding the importance of education, especially English in tourism areas; 2) Weak English language skills in tourism areas with great potential; 3) The community is unable to develop business in the tourism area because of inadequate English language skills; 4) Low community income. For this reason, PKM Pekan Baris formulates alternative solutions as follows: 1) Providing information on the importance of education and improving English language skills; 2) Conducting English language training for the people of Pasir Putih Village, Central Lombok; 3) Providing English-language training with business-oriented material that has been developed, but not developed and new businesses can be developed; 4) Increasing the diversity of businesses by utilizing the opportunities that exist, such as guides, renting surfing equipment and providing surfing training services, souvenir businesses that are the work of local communities. and the effort we form in the sustainability of the program, namely the massage business. The target line for the Week line includes: 1) Establishment of an English language training group in the village of Pasir Putih Selong Belanak; 2) Progress Report and Final Report on PKM Week Line implementation; 3) Scientific articles about the implementation of English language training for residents of the coast of Selong Belanak. The implementation method is carried out by direct training or speaking practice with the distribution of study groups according to age and conversation needs in the coastal area.